The Robotic revolution [videorecording] - Kight, Pal.; Larison, Elaine; Larison, June.; National Geographic Society, Washington, D.C. (Washington, D.C. The Society in cooperation with Oregon State University, 1986)
Shows how robots can assemble watches and automobiles, stock supermarket shelves, assist in surgery play the organ, and build other robots. Tells what a robot can and cannot do and examines the social implications of robots in the workplace.
VHS.
Narrator, John Flynn.
Keywords: Robotics; Robots, Industrial; Robots